2015
DOI: 10.4236/fns.2015.610092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet Supplementation with Food Industry By-Products on Diabetic Rats

Abstract: The present research work aimed to study the effects of 3 nutritional food industry by-products (orange peels, peanut skin peels and pomegranate peel) on regulating blood glucose level. 66 male adult Sprague-Dawely rats weighing 125 ± 5 g each were used. These rats were injected with alloxan for inducing diabetes. The negative control group consisted of rats fed on basal diet, while the positive control group consisted of (3 -11) sub-groups fed on basal diet in addition to 5%, 7.5% and 10% of nutritional food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Also, the best serum ALT were recorded for diabetic rats treated with psyllium seeds at 5%.While, the best serum AST and ALP were recorded for diabetic rats treated with psyllium husks at 5%. These results are in agreement with Elhardallou et al, (2015) founded that feeding on diet supplemented with psyllium, alone and combined, for four weeks to diabetic rats significantly decreased the levels of ALT, AST, and ALP enzymes in the serum compared with control positive group. Also, Zakia et al, (2018) they reported that Treatment with Psyllium extract significantly reduced ALT, AST and ALP enzymes after 4 weeks of treatment implying that the plant has executed a protective effect of liver damage.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the best serum ALT were recorded for diabetic rats treated with psyllium seeds at 5%.While, the best serum AST and ALP were recorded for diabetic rats treated with psyllium husks at 5%. These results are in agreement with Elhardallou et al, (2015) founded that feeding on diet supplemented with psyllium, alone and combined, for four weeks to diabetic rats significantly decreased the levels of ALT, AST, and ALP enzymes in the serum compared with control positive group. Also, Zakia et al, (2018) they reported that Treatment with Psyllium extract significantly reduced ALT, AST and ALP enzymes after 4 weeks of treatment implying that the plant has executed a protective effect of liver damage.…”
Section: Resultssupporting
confidence: 92%
“…In study Martin et al, (2012) showed that treated fatty liver rats with Psyllium recorded a high significant decrease (P≤0.01) in serum urea and creatinine when compared with control group. Also, Elhardallou et al, (2015) reported that leaves of C.intybus significantly reduced the level of serum urea in waster-albino rats. 5) indicate that positive control group had a significant increase in serum ALT, AST and ALP compared with negative control.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, de Bock et al (2012), found that psyllium husk supplementation with 6 g/day over 6 weeks, serum urea and creatinine levels were significantly lower (P>0.01) than in the control group. Elhardallou et al (2015), also reported that a diet enriched with psyllium husk lowered serum urea levels among rats. Elhassaneen et al (2021), reported that rats treated with psyllium husks at 5% significantly decreased values of urea in comparison to psyllium seeds, while no significant differences between them were shown for uric acid and creatinine.…”
Section: Resultsmentioning
confidence: 92%
“…These findings might be due to the components of psyllium husk "9,12octadecadienoic acid, methyl ester, and -sitosterol," which act as hepatoprotective agents (Devaraj et al, 2020). Likewise, Elhardallou et al (2015); Ali (2017), found that diabetic rats fed a diet enriched with psyllium seed husk, alone or in combination, for 4 weeks discovered a significant reduction in liver enzymes in comparison to the positive control group. The obtained findings were also in line with Hashem et al (2021), who found that psyllium husk ethanolic extract (250 g was extracted in 1L 70% ethanol) significantly reduced liver parameters in tritoninduced hyperlipidemic rats.…”
Section: Resultsmentioning
confidence: 98%
“…The chemical methods of nanoparticle synthesis are the most common approaches commercially employed in various areas of NP applications. Concurrently, plenty of research indicates a potential environmental threat of nanotechnology related to NP toxicity [111][112][113][114][115]. The chemical approach to NP synthesis is related to the use of toxic chemicals, which are hazardous to humans and the environment [116].…”
Section: Selenium Nanoparticles In Animal Nutritionmentioning
confidence: 99%